2022
DOI: 10.35188/unu-wider/2022/144-0
|View full text |Cite
|
Sign up to set email alerts
|

Recovery with distress: unpacking COVID-19 impact on livelihoods and poverty in Bangladesh

Abstract: This study is published within the UNU-WIDER project Transforming informal work and livelihoods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 2 publications
3
43
0
Order By: Relevance
“…This theme included 11 studies ( Ahmed et al, 2020 ; Begum et al, 2020 ; Bhuiyan et al, 2021 ; Bodrud-Doza et al, 2020 ; Emon et al, 2020 ; Hamadani et al, 2020 ; Islam, Islam et al, 2020 ; Mamun, 2021 ; Mamun et al, 2020 ; Mamun & Griffiths, 2020 ; Shammi et al, 2020 ), which reported the increase of “new poor” and suicide as a result of the long-term COVID-19 outbreak in Bangladesh. The new category of “new poor” refers to the Bangladeshi vulnerable non-poor who have fallen below the poverty line due to the impact of the COVID-19 crisis, but they were not poor before the pandemic ( Rahman et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…This theme included 11 studies ( Ahmed et al, 2020 ; Begum et al, 2020 ; Bhuiyan et al, 2021 ; Bodrud-Doza et al, 2020 ; Emon et al, 2020 ; Hamadani et al, 2020 ; Islam, Islam et al, 2020 ; Mamun, 2021 ; Mamun et al, 2020 ; Mamun & Griffiths, 2020 ; Shammi et al, 2020 ), which reported the increase of “new poor” and suicide as a result of the long-term COVID-19 outbreak in Bangladesh. The new category of “new poor” refers to the Bangladeshi vulnerable non-poor who have fallen below the poverty line due to the impact of the COVID-19 crisis, but they were not poor before the pandemic ( Rahman et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The current crisis in Bangladesh has exposed millions of informal workers, mostly poor and oppressed, and their families to hunger, malnutrition, and very bleak prospects. In the meantime, the research found that the cumulative poverty rate will be 40.9%, with a negative sales shock of 25.0%, which means another 20.4% of the Bangladeshi population, or 33.0 million people, will fall into poverty (Rahman and Matin, 2020). Our FGD findings showed,During Corona lockdown, I was unemployed for about 5–6 months, unable to work.…”
Section: Resultsmentioning
confidence: 99%
“…In this situation, they have to comply with many strategies to overcome hardship. In this regard, reduce expenses was one of the key coping strategies to maintain their life in the period of pandemic lockdown (Rahman and Matin, 2020). In formal migrants' life is like no job, no income.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The denoted here as LSR3'21 and LSR4'21, respectively (Rahman et al, 2022). They are referred to as Mar'21 and Sep'21 in the discussions.…”
Section: Methodsmentioning
confidence: 99%